Global impact of COVID-19 on corneal donor tissue harvesting and corneal transplantation - Mousavi, Morteza; Kahuam-López, Nicolás; Iovieno, Alfonso; Yeung, Sonia N. (Frontiers in Medicine, 2023)
Introduction The purpose of this review is to consolidate and examine the available literature on the coronavirus disease 2019 pandemic and its effect on corneal transplantation and eye banking. Methods A primary literature search was conducted using the PubMed (Medline) database with keywords and MeSH terms such as “corneal transplantation,” “eye banks,” “keratoplasty” and then were combined with COVID-19. Relevant articles through September 2022 were assessed and 25 articles were included in this review. Results Donor tissue volumes declined globally during lockdown periods due to a lower number of referrals and tighter tissue screening guidelines. Rates of elective surgeries decreased in the lockdown period compared to respective periods in previous years. However, changes in rates of emergency procedures were not uniform across different regions. Moreover, rates of different elective corneal grafts [i.e., penetrating keratoplasty (PK), endothelial keratoplasty (EK), or anterior lamellar keratoplasty (ALK)] were affected differently with the pattern of change being dependent on region-specific factors. Conclusion Both donor tissue volumes and rates of corneal transplant procedures were affected by lockdown restrictions. The underlying etiology of these changes differed by region. Examining the range of impact across many countries as well as the contributing factors involved will provide guidance for future global pandemics.